Network-based pharmacology and UHPLC-Q-Exactive-Orbitrap-MS reveal Jinhua Qinggan granule's mechanism in reducing cellular inflammation in COVID-19 - Qian, Liping; Zeng, Zehua (Frontiers in Immunology, 2024)
The emergence of the novel coronavirus SARS-CoV-2, the causative agent of a highly infectious pneumonia, represents a formidable challenge to global public health. To date, specific pharmacotherapies and vaccines are still in the developmental stage. Historically, Traditional Chinese Medicine (TCM) has played a significant role in combating pandemics, including those caused by influenza and other viral pneumonias. In our research, we investigated the effectiveness and pharmacological actions of Jinhua Qinggan Granules (JHQG) in the context of COVID-19. Initially, we conducted an analysis of JHQG's chemical constituents utilizing UHPLC-Q-Exactive-Orbitrap-MS, identifying a total of 73 components. Subsequent network pharmacological analysis and examination of single-cell RNA sequencing (scRNA-seq) data allowed us to determine that certain JHQG targets interact with immune cells from peripheral blood mononuclear cells (PBMCs). Moreover, a review of the literature corroborated the antiviral capacity of JHQG and its role in the amelioration of clinical symptoms and immune-inflammatory modulation. Our findings propose a mechanism for JHQG's efficacy in mitigating the inflammatory response and reducing the duration of inflammation in COVID-19 patients. Notably, the granules appear to inhibit the activity of specific immune cells, including activated neutrophil, monocytes, plasmoblasts, and effector T cells, preventing their overreaction in severe cases of the disease. In conclusion, our novel herb-constituent-target protein-cell network pharmacological approach elucidates JHQG's mechanism in tempering the inflammatory response of immune cells in peripheral blood, endorsing JHQG as both an effective and safe therapeutic option for influenza and viral pneumonia.